Teknik Menghafal Hadits Pendek Pada Anak Dengan Metode Gerakan Tangan - Syamsuriani Syamsuriani; Sukiman Sukiman (Universitas Cokroaminoto Palopo, 2024)
This research is motivated by issues in teaching the memorization of short Hadith at TK Yapis III Wosi Manokwari, where students' ability to memorize short Hadiths is still very low and has never reached the individual or class completion targets. This research is based on the notion that the ability to memorize Hadiths in early childhood is influenced by various factors, one of which is the method used. The objective of this research is to enhance the memorization skills of short Hadiths in early childhood through the implementation of the Hand Movement Method. The hypothesis posited is that the application of the Hand Movement Method is expected to improve the ability to memorize Hadiths in early childhood, and that female students perform better in memorizing Hadiths compared to male students. This research employs the Classroom Action Research method using the Kemmis & McTaggart model. The research subjects are 30 students aged 5-6 years in TK Yapis III Wosi Manokwari, consisting of 11 males and 19 females. Data collection techniques include performance assessment sheets, observation, documentation, and interviews. Data analysis is conducted through data reduction using both quantitative and qualitative approaches. The observation results indicate an increase in student engagement in the Hadith learning process after the implementation of the treatment. The research results show that by the end of Cycle II, the indicator of classical completion has been achieved, which is 83.33%, thus allowing the research to be concluded. The ability of female students to reach individual completion in memorizing Hadiths is better than that of male students when using the hand movement method. In conclusion, the research findings demonstrate that the application of the hand movement method in Hadith learning effectively enhances the ability to memorize Hadiths in 5-6-year-old children at TK Yapis III Wosi Manokwari. This research can serve as a reference for early childhood education institutions in developing creative and effective teaching methods.